PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN IPA BERBASIS PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA - Alin, Awalina Barokah; Kurnia, Ira Restu; Kalsum, Umi (Universitas Negeri Surabaya, 2023)
This study aims to determine the influence of the use of problem based learning science media on the scientific literacy skills. This study used pseudo-experimental research with a nonequivalent comparison-group design. The sample of this study was class IV A of 30 students who were treated with problem based learning science media and V B class which totaled 32 students with no treatment using problem based learning science media. Data collection was carried out with a test of scientific literacy skills that had been tested for validity and reliability. Data analysis using Univariate Analysis of Variance with 5% of significance level. The results showed that the difference in the average score of the pre-test was 65.50 while the average post-test score of interest in learning was 84.00. Problem based learning science media has a significant and positive effect on the scientific literacy skills seen from the calculation of 5,076 and P of 0.000; P=0.000<0.05;